2001
DOI: 10.1002/1521-4141(2001010)31:10<2919::aid-immu2919>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Vα gene replacement in a TCRα knock-in mouse

Abstract: Using a TCRα chain knock‐in mouse, we demonstrate that V‐gene replacement can operate in the T cell receptor α locus. Functional TCRα chain transcripts generated by Vα‐gene replacement at the site of the Vα‐embedded heptamer were identified in splenic T cells. This finding shows that Vα‐gene replacement can likely be used to shape the peripheral T cell repertoire.The conservation of the embedded heptamer in most Vα segments adds support to the notion that V‐gene replacement is a mechanism maintained to diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Endogenous TCR expression in the 5CC7 RAG-2-deficient mice could be mediated either by RAG-dependent recombination [13], gene conversion [14] or gene replacement [15] mechanisms involved in the generation of BCR and TCR diversity. To discriminate between these possibilities, we sequenced some of the TCRα and TCRβ-chains used by T-cells recovered from the allogeneic hosts.…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous TCR expression in the 5CC7 RAG-2-deficient mice could be mediated either by RAG-dependent recombination [13], gene conversion [14] or gene replacement [15] mechanisms involved in the generation of BCR and TCR diversity. To discriminate between these possibilities, we sequenced some of the TCRα and TCRβ-chains used by T-cells recovered from the allogeneic hosts.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism had already been described in receptor revision of both immunoglobulins and T cells (Golub, 2002;Golub et al, 2001;Itoh et al, 2000), although in this latter case it was limited to the TCR␣ locus. To our knowledge, this is the first report in which evidence of V-gene replacement, although indirect, is presented in the case of TCR␤.…”
Section: Tcr Revision In At Heterozygotesmentioning
confidence: 61%
“…Inefficient positive selection has been shown to result in the replacement of transgenic TCRα chains with α chains from the endogenous locus [25], [26]. It has also been shown that a rearranged VαJα gene segment that was introduced into the genomic Jα region was removed by secondary TCRα rearrangements when the selecting MHC allele was not present [27], [28]. We were not able to directly measure the loss of cell surface expression of the transgene encoded TCRα chain since a mAb specific for this Vα gene segment does not exist and a published I-A u :Ac1-11 tetramer was no longer available.…”
Section: Resultsmentioning
confidence: 99%